THE ROLE OF ISLAMIC CULTURAL HISTORY TEACHERS IN FORMING THE ISLAMIC CHARACTER OF GRADE IX STUDENTS AT NURUS SYAM WRINGIN BONDOWOSO MIDDLE SCHOOL - Izzul Kamal, Muhammad Nauval; Fawaid, Achmad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyse the role of Islamic Cultural History (SKI) teachers in shaping the Islamic character of class IX students at Madrasah Tsanawiyah Nurus Syam, Wringin, Bondowoso. A descriptive qualitative approach is used in this research, with data collection through observation, interview, and documentation. Research results show that SKI teachers have a strategic role as educators, mentors, and role models in the process of forming students' Islamic character. The strategies used include the integration of Islamic values in learning, familiarisation of noble morals, as well as strengthening through religious extracurricular activities. Success support factors include teacher commitment, school environment support, and parent participation. The challenges faced are the limited learning time and the heterogeneity of student character. This research concludes that SKI teachers play an important role in building students' Islamic character, so that a synergy between teachers, schools, and parents is needed to create an educational environment that supports the formation of Islamic character optimally.